Small spoon may be applied for effective weight management of youth with mild intellectual disabilities: Spoon Size and Intellectual Disabilities - Jung, Eun Young; Kim, Woon; Park, Eun-Young (Progress in Nutrition, 2023)
The purpose of this study was to investigate the effect of spoon size on food intake in people with intellectual disabilities. Curry rice (400 g) was served with different-sized spoons: normal spoon (8.3 cc) or small spoon (4.1 cc). Subjects ate significantly more when test meal was served with a normal spoon (498.1 g) as compared to a small spoon (442.6 g) (p < 0.05). Subjects took significantly more in each spoonful when test meal was served with a normal spoon (14.2 g) as compared to a small spoon (7.4 g). Eating rate was significantly different between a normal spoon (73.2 g/min) and a small spoon (58.8 g/min) (p < .05). The results of this study suggests that small spoon may be applied for effective weight management of youth with mild intellectual disabilities.